Preparation and characterization of positive electrode of NieMH batteries with cobalt additives - Ortiz, Mariela Gisela (2014)
The present paper shows the characterization and electrochemical behavior of alkaline batteries cathodes formed by nickel hydroxide with the addition of cobalt. This additive was incorporated by two methods: on the electrode surface, using the electroless technique and by direct incorporation of cobalt powder in the active material. The electrochemical behavior of both nickel hydroxide electrodes was investigated and compared. The results indicate that active materials containing cobalt additive by the electroless technique exhibit improved electrochemical performance.